Comparative Study of 0.75% Ropivacaine alone with 0.75% Ropivacaine and Dexmedetomidine Epidurally for Lower Limb & Lower Abdominal Surgery - Balwinder Kaur Rekhi; Babrah H; Punia TS (GMC Patiala Journal of Research and Medical Education, 2018)
Neuraxial adjuvants are used with local anaesthetic agents to enhance the quality of anaesthesia. The present study aimed at comparing the efficacy & safety of adding á2- adrenergic agonist, DEXMEDETOMIDINE to 0.75% Ropivacaine with Ropivacaine alone epidurally for lower limb & lower abdominal surgery. It was concluded that addition of Dexmedetomidine to local anaesthetic agent Ropivacaine 0.75% epidurally as an adjuvant provides better sensory and motor block, intraoperative sedation and prolonged postoperative analgesia.